Tick abundance and life-stage segregation on the American black bear (Ursus americanus). (December 2021) - Tiffin, Hannah S.; Skvarla, Michael J.; Machtinger, Erika T.
Abstract: Tick abundance and diagnosed cases of tick-borne diseases have been increasing in the United States. American black bear ( Ursus americanus ) populations have also been increasing in the eastern United States. As a competent host of several species of ticks and a mammal capable of traveling long distances, the role of black bears as hosts for ticks requires further evaluation. Ectoparasite surveys were conducted on black bears in Pennsylvania to evaluate tick presence, abundance, spatial distribution, and association with Sarcoptes scabiei, the etiological agent of sarcoptic mange, on bears to better understand their role in tick ecology and to improve on-host surveillance techniques. Tick burden was evaluated using standard area sampling (10.16 × 10.16 cm squares) on pre-designated body regions on black bears from June 2018–December 2019. In total, 278 unique individual black bears were evaluated, with all ticks identified as Ixodes scapularis ( n  = 1976; 76.7% adults, 23.3% immatures). Tick presence differed by body region on bears, with the highest percentage of tick observations located on bear ears and muzzle. Ticks also partitioned on black bears by life-stage, with immature ticks primarily recorded on the lower extremities of bears and adult ticks primarily recorded on the front-quarters of bears. This includes the first known record of I. scapularis larvae parasitizing black bears, and observations of all three mobile life-stages concurrently parasitizing bears. Tick abundance was also statistically significant dependent on season, with the highest abundance of ticks recorded in spring and lowest abundance in fall. Adult ticks were less likely to be present on bears with mange. These data reveal the important role black bears may serve in tick ecology and dispersal as all three mobile life-stages of I. scapularis were found parasitizing a mammal capable of traveling far distances in a region with high numbers of Lyme disease cases. Graphical abstract: Image 1 Highlights: First record of Ixodes scapularis larvae parasitizing black bears. All three I. scapularis mobile life-stages concurrently parasitizing black bears. I. scapularis life-stage segregation on black bears. Standardized tick survey findings can be used to improve on-host surveillance. Bears with sarcoptic mange less likely to have adult ticks present.